A case of an epithelioid glioblastoma with the BRAF V600E mutation colocalized with BRAF intact low‐grade diffuse astrocytoma. Issue 2 (16th September 2015) - Kuroda, Jun‐Ichiro; Nobusawa, Sumihito; Nakamura, Hideo; Yokoo, Hideaki; Ueda, Ryuta; Makino, Keishi; Yano, Shigetoshi; Kuratsu, Jun‐ichi
Abstract : Epithelioid glioblastomas are one of the rarest histological variants of glioblastomas, which are not formally recognized by the World Health Organization (WHO) classification. Epithelioid glioblastomas usually occur as primary lesions, but there have been several reports of secondary epithelioid glioblastomas or epithelioid glioblastomas with pre‐ or co‐existing lesions to date. The serine/threonine‐protein kinase B‐Raf (BRAF) V600E mutation has been found at a high frequency of 54% in epithelioid glioblastomas. We present a case of a 26‐year‐old female patient with an epithelioid glioblastoma with the BRAF V600E mutation in her right frontal lobe. In the present case, a low‐grade diffuse astrocytoma component had colocalized with the epithelioid glioblastoma. The component presented prominent calcification on neuroimages as well as by histology, and low‐grade diffuse astrocytoma was considered to be a precursor lesion of an epithelioid glioblastoma. However, the BRAF V600E mutation was detected only in epithelioid glioblastoma but not in low‐grade diffuse astrocytoma. To the best of our knowledge, this is the first report demonstrating a discrepancy in the BRAF V600E mutation states between epithelioid glioblastoma and colocalized low‐grade astrocytoma.